Control interno del capital de trabajo en las PYMES del sector camaronero - Moreira Peña, Liz Kerly (2020)
This research work focuses on the analysis of internal control over the working capital of shrimp SMEs. Companies that have adequate management of working capital have the advantage of obtaining benefits such as permanence over time, greater competitiveness among SMEs and achieving the proposed objectives. The administration of the capital of the working capital is of vital importance for a good liquidity management of SMEs since it is about managing current assets, current liabilities and being able to cover short-term obligations. The research is divided as follows……